2014
DOI: 10.1039/c3sm52856a
|View full text |Cite
|
Sign up to set email alerts
|

Styrene–butadiene–styrene copolymer compatibilized carbon black/polypropylene/polystyrene composites with tunable morphology, electrical conduction and rheological stabilities

Abstract: We report a facile kinetic strategy in combination with styrene-butadiene-styrene (SBS) copolymer compatibilizers for preparing carbon black (CB) filled immiscible polypropylene (PP)/polystyrene (PS) (1/1) blends with finely tuned morphologies and show the important role of location and migration of CB nanoparticles in determining the electrical conductivity and rheological behaviour of the composites. A novel method of mixing a SBS/CB (5/3) masterbatch with the polymers allowed producing composites with CB ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
33
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 74 publications
(105 reference statements)
4
33
0
Order By: Relevance
“…It has been found that significant variations of mechanical, thermal, electrical and barrier property occurred even if incorporated nanofillers at a very low loadings [1][2][3][4][5][6][7][8]. Graphene is regarded as the strongest material to date by theoretical and experimental results and chemically the most reactive form of carbon due to the lateral availability of carbon atoms [9].…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that significant variations of mechanical, thermal, electrical and barrier property occurred even if incorporated nanofillers at a very low loadings [1][2][3][4][5][6][7][8]. Graphene is regarded as the strongest material to date by theoretical and experimental results and chemically the most reactive form of carbon due to the lateral availability of carbon atoms [9].…”
Section: Introductionmentioning
confidence: 99%
“…[3] BPA finds use in a myriad of products from adhesives, flame retardants, and electronics insulation to optical lenses, paper coatings, containers for food and beverages, and hybrid materials such as carbon and glass fiber composites. [9,16,17] Even once polymerized, BPA-containing polymers exhibit residual BPA-based monomer content that can leach into contacting fluids or be absorbed through contacting biological material, such as skin. [9] Despite their deleterious effects and source sustainability issues, polymer resins containing BPA are easily processed and afford excellent high-performance properties (glass transition temperatures (T g 's) between 70 and 250 °C, modulus at 25 °C between 2 and 4 GPa, flexural strength greater than 100 MPa, and fracture energy greater than 100 J m −2 ) stemming from the high degree of molecular rigidity imparted by the aromatic rings and relatively bulky isopropylene bridge.…”
mentioning
confidence: 99%
“…There have been many studies engaged to expand the application fields of SBS, such as getting SBS modified with different functional groups or incorporating various fillers into SBS matrix . Among them it is practical to design carbon black as fillers to improve the mechanical property and impart it with some functionalities, such as electrical conductivity, thermal conductivity, and permeability resistance . Nevertheless, too much carbon black impedes the microphase separation of SBS and strongly deteriorates the mechanical properties of the resulting composite .…”
Section: Introductionmentioning
confidence: 99%